2015
DOI: 10.1007/s12591-015-0243-0
|View full text |Cite
|
Sign up to set email alerts
|

Triangular Libration Points in the CR3BP with Radiation, Triaxiality and Potential from a Belt

Abstract: In this paper the equations of motion of the circular restricted three body problem is modified to include radiation of the bigger primary, triaxiality of the smaller primary; and gravitational potential created by a belt. We have obtained that due to the perturbations, the locations of the triangular libration points and their linear stability are affected. The points move towards the bigger primary due to the resultant effect of the perturbations. Triangular libration points are stable for 0 < μ < μ c and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The importance of the problem in astronomy has been addressed by Yeh (2004, 2006), where it was shown that the presence of disk resulted in additional equilibrium points of the system. Other works that took into account the gravitational potential from the belt/disk under different assumptions include Singh and Taura (2013, 2015, 2017 and Jiang and Yeh (2014). This image shows a dramatic scorched extrasolar planet HD 209458b in its orbit around a yellow Sun-like star.…”
Section:  mentioning
confidence: 99%
“…The importance of the problem in astronomy has been addressed by Yeh (2004, 2006), where it was shown that the presence of disk resulted in additional equilibrium points of the system. Other works that took into account the gravitational potential from the belt/disk under different assumptions include Singh and Taura (2013, 2015, 2017 and Jiang and Yeh (2014). This image shows a dramatic scorched extrasolar planet HD 209458b in its orbit around a yellow Sun-like star.…”
Section:  mentioning
confidence: 99%
“…He called the CR3BP, photogravitational when one or both of the masses of the primaries were discharges of radiation. Researchers [6]- [10] have examined the existence of libration points and their linear stability in the photogravitational CR3BP. [11] [12] studied a modified CR3BP by considering the influence from a belt (circular cluster of material points) for planetary systems and found that the likelihood to get libration points around the inner part of the belt was greater than the one nigh the outer part.…”
Section: Introductionmentioning
confidence: 99%